On Schauder Frames in Conjugate Banach Spaces - S. K. Kaushik; S. K. Sharma; Khole Timothy Poumai (Journal of Mathematics)
Weak*-Schauder frame in conjugate Banach spaces has been introduced and studied. A sufficient condition for the existence of weak*-Schauder frame in the conjugate space of a separable Banach space has been given. It has been shown that has weak*-Schauder frame. Finally, a sufficient condition for the existence of a Schauder frame sequence has been given.